Reformas al código del trabajo, incorporando normas que permitan garantizar la eficacia del debido proceso en el trámite de las controversias laborales, y asegurar el pago de las remuneraciones adeudadas del trabajador - Castro Castillo, Priscila Verenisse (2016)
This work of legal investigation takes for title: "Reforms to the Code of the Work, incorporating norms that allow to guarantee the effectiveness of the due process in the step of the labor controversies, and to assure the payment of the worker's owing remunerations", their development was considered when verifying the nonfulfillment of the principle of velocity procedural and due process in the labor trials where so that the worker was able to charge his remunerations claimed in the trial he should hope the Judge dictates sentence condemnatory ejecutoriada, contrary case he cannot make effective his right to the opportune remuneration. Being authorized starting from the sentence condemnatory non ejecutoriada to require measured precautelatorias, the same ones that are dictated inopportunely because until so much, the employer already transferred the domain of their patrimony to other people and it doesn't have resources to pay. This way they are in helplessness the worker's labor rights. The theoretical, juridical and doctrinal storing, the study of concrete cases, the application of surveys and interviews, he/she allowed to obtain approaches with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of the objectives and the contrasting from the relating outlined hypothesis to this practice; so much the Constitution of the Republic of the Ecuador, as the other laws labor typify the rights of the workers.